2019
DOI: 10.1371/journal.pone.0222360
|View full text |Cite
|
Sign up to set email alerts
|

Combining fish and environmental PCR for diagnostics of diseased laboratory zebrafish in recirculating systems

Abstract: Precise knowledge of the health status of experimental fish is crucial to obtain high scientific and ethical standards in biomedical research. In addition to the use of sentinel fish, the examination of diseased fish is a fundamental part of all health monitoring concepts. PCR assays offer excellent sensitivity and the ability to test a broad variety of pathogenic agents in different sample types. Recently, it was shown that analysis of environmental samples such as water, sludge or detritus from static tanks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Previous studies have reported that environmental samples are not adequate for the detection of the microsporidium in zebrafish facilities (Crim et al 2017;Miller et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that environmental samples are not adequate for the detection of the microsporidium in zebrafish facilities (Crim et al 2017;Miller et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that environmental samples are not adequate for the detection of the microsporidium in zebrafish facilities (Crim et al 2017; Miller et al 2019). However, this conclusion was based on the sampling of flowing water from aquaria and a sample processing method that did not incorporate a sonication step to disrupt spores as previously recommended (Sanders and Kent 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for early detection methods lay on molecular techniques that detect the pathogen even prior the infection. Recently, and to complement PCR analysis of fish, Miller et al (2019) tested the detection of P. neurophilia by using real-time PCR taking environmental samples such as water, sludge or detritus from the tanks. However, this approach was not sensitive enough for P. neurophilia detection, contrary to what happened with mycobacteria and Myxidium streisingeri, which were mainly identified in environmental samples (Miller et al 2019).…”
Section: Molecular Analysismentioning
confidence: 99%
“…et al (2011), Peterson et al (2011), Sanders et al (2013), Sanders et al (2014), Spagnoli et al screen large numbers of fish. Require very little tissue, it can be adapted to screen water sources, and detect all life stages of the pathogen As assay is specific to only a single pathogen, it is used as a follow-up to histology Whipps and Kent (2006), Murray et al (2011), Spagnoli et al (2015b),Miller et al (2019) of the fish in which the parasite has been found, tissues/organs in which it was present, further comments, reliability scale and references are shown. Reliability scale based on the fulfilment of the following requirements by the method: (A) useful in all live stages of the fish; (B) reliability in detecting mature spores; (C) reliability in detecting presporogonic stages of the parasite; (D) none or small amount of tissue sample/ environmental (i.e.…”
mentioning
confidence: 99%